Las actividades académico profesionales en los niveles de estrés en los docentes universitarios de la Facultad de Ciencias de la Educación de la Universidad Nacional de Chimborazo - Bonilla Colcha, Edison Armando (2022)
This research addressed the issue of academic-professional activities on stress levels in university professors of the Faculty of Educational Sciences of the National University of Chimborazo. During this pandemic, many professors increased their stress levels due to the occupations involved in their professional practice and their functions within the University. They fulfill different roles such as teaching, research, direction, academic management, and activities related to society. The study's main objective was to determine the relationship between academic-professional activities and stress levels of university professors at the Faculty of Education Sciences of the National University of Chimborazo. A methodology with a quantitative approach, non-experimental design, hypothetical-deductive method, correlational scope, fundamental objective, field and bibliographic location, and cross-sectional time was proposed. On the other hand, the study population was 152 professors of the Faculty of Educational Sciences, Humanities and Technologies, while the sample size was 72 professors obtained non-probabilistic. In addition, the development of the theoretical perspective was based on the review of academic documentation. In turn, for the data collection of the variables, a questionnaire was used to determine the academic-professional activities. The Cohen Perceived Stress Scale (PSS) was used for the variable of stress levels. The research hypothesis, tested through Pearson's Chi2, stated that there is no relationship between academic and professional activities and stress levels in university professors of the Faculty of Education Sciences of the National University of Chimborazo. In conclusion, it was determined that there is no relationship between the study variables, and it was also identified that the academic professional activities are teaching, research, direction, and academic management, as well as the link with society. However, it is worth mentioning that the predominant activity is teaching, and professor’s level is acute episodic stress.